2002
DOI: 10.1038/sj.leu.2402390
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic variables in newly diagnosed children and adolescents with acute myeloid leukemia: Children's Cancer Group Study 213

Abstract: The objective of this study was to identify biologic parameters that were associated with either exceptionally good or poor outcome in childhood acute myeloid leukemia (AML). Among the children with AML who entered Children's Cancer Group trial 213, 498 patients without Down syndrome or acute promyelocytic leukemia (APL) comprise the basis for this report. Univariate comparisons of the proportion of patients attaining complete remission after induction (CR) indicate that, at diagnosis, male gender, low platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 24 publications
9
32
0
2
Order By: Relevance
“…Other prognostic factors identified in our analysis have been reported in other studies as important predictors of outcome, including kidney disease (23,27,28), hepatomegaly (29), and bleeding (30). The presence of the FAB M2 subgroup was protective, possibly as a consequence of the relationship between FAB M2 subgroup and well-defined prognostic factors such as t(8;21) translocation (31), and a lower frequency of FLT3 mutations (32).…”
Section: Discussionsupporting
confidence: 69%
“…Other prognostic factors identified in our analysis have been reported in other studies as important predictors of outcome, including kidney disease (23,27,28), hepatomegaly (29), and bleeding (30). The presence of the FAB M2 subgroup was protective, possibly as a consequence of the relationship between FAB M2 subgroup and well-defined prognostic factors such as t(8;21) translocation (31), and a lower frequency of FLT3 mutations (32).…”
Section: Discussionsupporting
confidence: 69%
“…The most important prognostic factor according to NOPHO-AML 93 was the response to the first course of therapy as also reported by others. 18,19 Children with persistent disease after the first course received a different and more toxic induction therapy, while responding children were spared of such intensification. Although they received less intensive treatment, the EFS and DFS values for good responders were significantly superior as compared to the poor responders.…”
Section: Discussionmentioning
confidence: 99%
“…28,37,38 Indeed, as being demonstrated in a large study of 680 AML patients, CR rates of patients with intermediate karyotype but day 16 blasts o10% were comparable to the cohort with favorable cytogenetics. 39 Wells et al 40 demonstrated in 498 pediatric patients that a threshold of X15% BM blasts on day þ 14 after the start of induction therapy was associated with lower remission rates. Thus, persistence of higher blast percentages once induction is completed should always raise concern whether there might be an indication for allo-SCT.…”
Section: Cytomorphologymentioning
confidence: 99%